2017
DOI: 10.3892/ijmm.2017.3229
|View full text |Cite
|
Sign up to set email alerts
|

Cryptdin-2 predicts intestinal injury during heatstroke in mice

Abstract: Intestinal injury-induced bacterial translocation and endotoxemia are important in the pathophysiological process of heatstroke. However, the underlying mechanism remains to be fully elucidated. Previous studies using 2D-gel electrophoresis found that defensin-related cryptdin-2 (Cry-2), an intestinal α-defensin, is upregulated in intestinal tissues during heatstroke in mice, and that treatment with ulinastatin, a multivalent enzyme inhibitor, reduced heat-induced acute lung injury. To investigate the associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 49 publications
5
23
0
Order By: Relevance
“…Besides, piglets fed ICA and pICA showed a lower diarrhea rate after suffering from ETEC K88 infection. 38 Besides, ETEC K88 infection reduced the transmembrane resistance of IPEC-J2 cells and increased FITC-D4 flux, which was consistent with previous study. CON: cells were not any treated for 15 hours.…”
Section: Discussionsupporting
confidence: 92%
“…Besides, piglets fed ICA and pICA showed a lower diarrhea rate after suffering from ETEC K88 infection. 38 Besides, ETEC K88 infection reduced the transmembrane resistance of IPEC-J2 cells and increased FITC-D4 flux, which was consistent with previous study. CON: cells were not any treated for 15 hours.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, a relatively higher histopathological score indicated that the morphological structure of the colonic and caecal epithelia of LBW pigs suffered from varying degrees of damage. The chemical markers (DAO and D-lactate) are usually low in the circulation system in healthy individuals and will have a significant increase in the circulation system during the destruction of the intestinal barrier (36). Our data show the levels of DAO and D-lactate in plasma were significantly increased in the LBW group, implying increases in the intestinal permeability of LBW pigs.…”
Section: Discussionmentioning
confidence: 59%
“…Decreased production of SCFAs by the microbiota increases disruption of the gut barrier 21 . In verifying the damage of the intestinal mucosa, large increases of D-Lac and DAO, chemical markers that are usually high in serum during the destruction of the intestinal barrier, were observed in anti-NMDAR encephalitis patients 22 . Therefore, the lack of protection from anti-inflammatory metabolites of beneficial bacteria and abnormal intestinal permeability also play key roles in the pathogenesis of anti-NMDAR encephalitis.…”
Section: Discussionmentioning
confidence: 97%